2023
DOI: 10.3390/nano13091528
|View full text |Cite
|
Sign up to set email alerts
|

BiVO4 As a Sustainable and Emerging Photocatalyst: Synthesis Methodologies, Engineering Properties, and Its Volatile Organic Compounds Degradation Efficiency

Abstract: Bismuth vanadate (BiVO4) is one of the best bismuth-based semiconducting materials because of its narrow band gap energy, good visible light absorption, unique physical and chemical characteristics, and non-toxic nature. In addition, BiVO4 with different morphologies has been synthesized and exhibited excellent visible light photocatalytic efficiency in the degradation of various organic pollutants, including volatile organic compounds (VOCs). Nevertheless, the commercial scale utilization of BiVO4 is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 139 publications
0
11
0
Order By: Relevance
“…Environmental pollutants, including organic and inorganic pollutants, pose a serious threat to the natural environment and human health [ 88 ]. BiVO 4 and BiVO 4 -based composites, which are non-toxic to the environment, can effectively degrade various organic and inorganic pollutants in water bodies [ 89 , 90 ]. In this study, the efficiency of BiVO 4 -based composites in degrading environmental pollutants under various conditions was investigated in order to better understand the photocatalytic performance of various composites.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental pollutants, including organic and inorganic pollutants, pose a serious threat to the natural environment and human health [ 88 ]. BiVO 4 and BiVO 4 -based composites, which are non-toxic to the environment, can effectively degrade various organic and inorganic pollutants in water bodies [ 89 , 90 ]. In this study, the efficiency of BiVO 4 -based composites in degrading environmental pollutants under various conditions was investigated in order to better understand the photocatalytic performance of various composites.…”
Section: Resultsmentioning
confidence: 99%
“…103,107 An earlier study by Kudo et al 108 has shown that BiVO 4 exhibits broad-spectrum absorption under ultraviolet and visible light, causing high photocatalytic activity. Since then, significant studies have been carried out on the unique and excellent photoelectric properties of BiVO 4 and suggest a wide range of applications in fields such as organic pollutant degradation, 109 water splitting, 110 CO 2 reduction, 111 and photoanodes. 112 In order to further improve the photocatalytic activity, visible light absorption intensity, and other photoelectric properties of BiVO 4 , researchers have also attempted to improve the high electron–hole recombination rate and poor electron mobility of BiVO 4 by element doping, 113 vacancy introduction, 114 or heterostructure construction.…”
Section: Classification Of Bismuth-based Semiconductorsmentioning
confidence: 99%
“…Bi-based materials have been widely applied in photocatalysis because of their suitable band gap, excellent visible light response, low cost, high stability, and non-toxicity. 41–43 However, Bi-based materials inevitably have some disadvantages, such as fast recombination of photo-generated electron–hole pairs and poor electron transfer kinetics, which lead to unsatisfactory catalytic activity. 44 Moreover, partial Bi-based catalysts, such as Bi 2 WO 6 , BiVO 4 , BiFeO 3 , BiOIO 3 , etc ., have piezoelectric properties, 15,45,46 and are denoted as Bi-based non-centrosymmetric materials.…”
Section: The Structural Optical and Piezoelectric Properties Of Bi-ba...mentioning
confidence: 99%